Islamic Boarding School Students' Motivations and Challenges in English Language Learning: A Case Study at Nurul Hakim Islamic Boarding School: Motivasi dan Tantangan Santri Pesantren dalam Pembelajaran Bahasa Inggris: Studi Kasus di Pesantren Nurul Hakim - Azzura, M Ragil Dwifani; Dewi Saniati (Pesantren Reviews, 2023)
This research study examined the students' motivations and challenges in English language learning at Nurul Hakim Islamic Boarding School. The research methodology employed qualitative data collection techniques, including interviews and observations, to gather in-depth information from 10 Nurul Hakim Islamic Boarding School students as the sample. The findings of this study reveal several key motivations expressed by the students, such as job opportunities, cultural exchange, effective communication, personal development and prospects. The research also identifies significant challenges faced by the students, including language difficulties, understanding spoken English, reading and writing, frustration and hesitation, and listening and comprehension. Based on the research findings, it was concluded that the identified motivations and challenges of students in learning English at Nurul Hakim Islamic Boarding School highlight the significance of addressing these factors to enhance English language acquisition. By addressing the primary motivations of students and overcoming the specific challenges they face, tailored instructional strategies could be implemented to promote learner autonomy and create a supportive learning environment, thus fostering effective English language learning at Nurul Hakim Islamic Boarding School.